Depth Evaluation of Slits on Galvanized Steel Plate Using A Low Frequency Eddy Current Probe - N. A., Nadzri; M. M., Saari; M. A. H. P., Zaini; A. M., Halil; A. J. S., Hanifah; M., Ishak (Springer Singapore, 2020)
This study performs an analysis of a small eddy current probe config-uration based on differential anisotropic magnetoresistance (AMR) sensors for characterization of small surface defects in galvanized steel plates. Owing to the advantage of the AMR sensor, the system of eddy current testing (ECT) with the AMR sensor has a huge benefit to detect sub-millimeter defects in steel struc-tures. In this study, an ECT probe is developed by using AMR sensors to perform crack detection in 2-mm galvanized steel plates with regards to the depth of arti-ficial slits where the ECT probe is scanned above the slits’ area. The signal that is detected by a lock-in amplifier is investigated with different frequencies of an excitation field. The line-scanned of signal intensity shows a clear intensity change at the crack area. This signal depends on the depth and frequencies. Fi-nally, a correlation between depth and detected signals is clarified with respect to different frequencies.